2002
DOI: 10.1097/00004872-200212000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Regression of ventricular and vascular hypertrophy

Abstract: ACEIs reduce cardiovascular hypertrophy uniformly via an AT -receptor- mediated mechanism, reinforcing the opinion that ACEI effects are indeed class effects. The significance of local renin-angiotensin systems was confirmed by antihypertrophic effects in the aorta that were apparent in the absence of any blood pressure reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This observation indicates that not only endogenously infused AII, but also endogenously produced AII is able to activate PARP in the vasculature. The dose of enalapril used in the current study has been shown to provide a full blockade of angiotensin-converting enzyme (ACE) and has been demonstrated to normalize blood pressure and cardiovascular function (28)(29)(30). The question may arise as to whether PARP activation in SHR animals is related to AII directly activating oxidative and nitrosative processes in the endothelial cells, or alternatively, to the physical phenomenon of hypertension, which could, in theory, enhance endothelial oxidant and free radical production via increased shear stress (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicates that not only endogenously infused AII, but also endogenously produced AII is able to activate PARP in the vasculature. The dose of enalapril used in the current study has been shown to provide a full blockade of angiotensin-converting enzyme (ACE) and has been demonstrated to normalize blood pressure and cardiovascular function (28)(29)(30). The question may arise as to whether PARP activation in SHR animals is related to AII directly activating oxidative and nitrosative processes in the endothelial cells, or alternatively, to the physical phenomenon of hypertension, which could, in theory, enhance endothelial oxidant and free radical production via increased shear stress (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…The diet was abundantly offered, supplementary to chow, whereas controls received chow only (Miesel et al 2010). At regular intervals, blood pressure and heart rate were determined by plethysmography (Raasch et al 2002) and blood samples were withdrawn from a tail nick to measure blood glucose, plasma aldosterone and S1P levels. For S1P-induced aldosterone release, 200 µg/kg S1P was intravenously injected as described earlier in chow-vs CD-fed SHRs.…”
Section: S1p Effects On Plasma Aldosterone Of Diet-induced Obese Pitmentioning
confidence: 99%